Nanocatalysts - Sinha, Indrajit; Shukla, Madhulata (IntechOpen, 2019)
Nanocatalysis is a topical area of research that has huge potential. It attempts to merge the advantages of heterogeneous and homogeneous catalysis. The collection of articles in this book treats the topics of specificity, activity, reusability, and stability of the catalyst and presents a compilation of articles that focuses on different aspects of these issues.